Prediction of trough concentration and ALK occupancy in plasma and cerebrospinal fluid using physiologically based pharmacokinetic modeling of crizotinib, alectinib, and lorlatinib - Li, Bole; Liu, Shan; Feng, Honglei; Du, Chunshuang; Wei, Liman; Zhang, Jie; Jia, Guangwei; Wu, Chunnuan (Frontiers in Pharmacology, 2023)
Brain metastases occur in approximately 30% of patients with non-small cell lung cancer (NSCLC). Therefore, the free drug concentration in cerebrospinal fluid (CSF) is strongly associated with clinical efficacy. The present study aimed to develop the physiologically based pharmacokinetic (PBPK) models that can predict the steady-state trough concentration (Ctrough) in plasma and CSF, as well as ALK occupancy (AO) for three inhibitors: crizotinib (CRI), alectinib (ALE), and lorlatinib (LOR). To achieve this, population PBPK models were successfully developed and validated using multiple clinical pharmacokinetics (PK) and drug-drug interaction (DDI) studies, both in healthy subjects and patients. The prediction-to-observation ratios for plasma AUC, Cmax and Ctrough in heathy subjects and patients ranged between 0.5 and 2.0. Additionally, the PK profiles of CRI, ALE and LOR in CSF aligned well with the observed data. Moreover, the AUC and Cmax ratios of the three inhibitors when co-administered with CYP3A4 inhibitors/inducers also matched clinically observed values. Utilizing PK thresholds for effective plasma Ctrough and AO values on wild-type and four ALK mutations in plasma and CSF, the PBPK models were then combined with the mean and 95% confidence interval to predict optimal dosing regimens. Overall, these PBPK models provide valuable insights into determining appropriate dosing regimens for the three ALK inhibitors, understanding their effectiveness in brain metastases therapy, and analyzing the underlying mechanisms of on-target resistance.